Pedagogical Efficacy of Learning from the Built Environment through Real-life Experiences: A Case Study from Communities around Si Satchanalai Historical Park - Koompong Noobanjong; Chaturong Louhapensang (My University, 2017)
In early 2017, a combined team of faculty members and students from King Mongkut’s Institute of Technology, Ladkrabang (KMITL) and Ball State University (BSU), U.S.A., conducted a three-week field study in three neighborhoods around Si Satchanalai Historical Park, one of UNESCO World Heritage sites in Thailand. Drawing on the concepts of Coordination, Cooperation, and Collaboration (3Cs), the Thai and foreign students jointly created several spatial maps to record their encounters with the livelihood—along with artistic and architectural heritages, as well as social and cultural practices—in Nong O, Sarachit, and Dong Khu sub-districts in Sukhothai province. The abovementioned activities supplied the contextual basis for this research to assess the pedagogical efficacy of learning from real-life experiences via the spatial mapping projects in those communities. Informed by Bloom’s taxonomies of learning, the upcoming evaluative discussions contained a series of independent sample t-tests, utilizing a number of questionnaires and surveys for collecting data to construct a content model in terms of comparative studies between the KMITL and BSU members. In effect, the statistical inquiries disclosed that not only did the participants advance their cross-cultural interactions and understanding with each other, but also gained a higher body of knowledge apart from developing many crucial skills, such as critical and creative thinking capabilities. The qualitative investigations further exhibited that the 2017 KMITL-BSU fieldwork contributed several scholarly improvements, resulting in academic achievements by the partakers from both universities.
Keywords: Geography Education and Pedagogy